Transformasi Digital dalam Industri Halal di Indonesia (Studi Implementasi Teknologi Blockchain dalam Proses Sertifikasi Halal) - Arlinta Prasetian Dewi; Mohammad Ichsan Hakiki (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Technological transformation in the halal industry in Indonesia is a necessity. In this case, the government wants to integrate blockchain technology into the halal certification management process. This research aims to determine the extent to which these opportunities can be exploited and the possible consequences that will occur. The method used uses qualitative methods by observing phenomena that occur in society. The results obtained are that BPJPH as an institution that issues halal certification before integrating with blockchain technology must carry out improvements and review the halal system as well as educate business actors, assistants and parties related to the process of issuing halal certificates